Cloning and expression of the cDNA encoding rat granulocyte colony-stimulating factor - Han, Sang Won [UNESP]; Ramesh, N.; Osborne, William R.A. (Elsevier, 1996)
Granulocyte colony-stimulating factor (G-CSF) acts on precursor hematopoietic cells to control the production and maintenance of neutrophils. Recombinant G-CSF (re-G-CSF)is used clinically to treat patients with neutropenia and has greatly reduced the infection risk associated with bone marrow transplantation. Cyclic hematopoiesis, a stem cell defect characterized by severe recurrent neutropenia, occurs in man and grey collie dogs, and can be treated by administration of re-G-CSF. Availability of the rat G-CSF cDNA would benefit the use of rats as models of gene therapy for the treatment of cyclic hematopoiesis. In preliminary rat experiments, retroviral-mediated expression of canine G-CSF caused neutralizing antibody formation which precluded long-term increases in neutrophil counts. To overcome this problem we cloned the rat G-CSF cDNA from RNA isolated from skin fibroblasts. The rat G-CSF sequence shared a high degree of identity in both the coding and non-coding regions with both the murine G-CSF (85%) and human G-CSF (74%). The signal peptides of murine and human G-CSF both contained 30 amino acids (aa), whereas the deduced signal sequence for rat G-CSF possessed 21 aa. A retrovirus encoding the rat G-CSF cDNA synthesized bioactive G-CSF from transduced vascular smooth muscle cells.
Keywords: Gene therapy; Neutropenia; Nucleotide sequence; complementary dna; granulocyte colony stimulating factor; neutralizing antibody; recombinant granulocyte colony stimulating factor; animal cell; animal experiment; animal model; bone marrow transplantation; dog; gene therapy; graft infection; hematopoiesis; hematopoietic cell; human; human cell; molecular cloning; neutropenia; neutrophil; nonhuman; priority journal; rat; retrovirus; stem cell; vascular smooth muscle; Amino Acid Sequence; Animals; Base Sequence; Cloning, Molecular; DNA, Complementary; Genetic Vectors; Granulocyte Colony-Stimulating Factor; Mice; Molecular Sequence Data; Rats; Sequence Analysis, DNA; Sequence Homology; Animalia; Canis familiaris; Murinae; unidentified retrovirus